2019
DOI: 10.3390/v11090821
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Enterovirus D68-Induced Neurologic Disease: A Basic Science Review

Abstract: In 2014, the United States (US) experienced an unprecedented epidemic of enterovirus D68 (EV-D68)-induced respiratory disease that was temporally associated with the emergence of acute flaccid myelitis (AFM), a paralytic disease occurring predominantly in children, that has a striking resemblance to poliomyelitis. Although a definitive causal link between EV-D68 infection and AFM has not been unequivocally established, rapidly accumulating clinical, immunological, and epidemiological evidence points to EV-D68 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 102 publications
(198 reference statements)
1
53
0
2
Order By: Relevance
“…[37][38][39] In the case of EV-D68-associated AFM, nasopharyngeal and throat swabs are frequently positive for virus by RT-PCR when obtained early after disease onset, yet, CSF RT-PCR tests are only positive in a small minority (<3%) of cases. 40 The sensitivity of SARS-CoV-2 RT-PCR in properly performed nasopharyngeal swabs for detection of acute COVID-19 is high, but data are currently too limited to evaluate sensitivity of this technique in CSF in patients with neurological disease.…”
Section: Neuroinvasion By Sars-cov-2mentioning
confidence: 99%
“…[37][38][39] In the case of EV-D68-associated AFM, nasopharyngeal and throat swabs are frequently positive for virus by RT-PCR when obtained early after disease onset, yet, CSF RT-PCR tests are only positive in a small minority (<3%) of cases. 40 The sensitivity of SARS-CoV-2 RT-PCR in properly performed nasopharyngeal swabs for detection of acute COVID-19 is high, but data are currently too limited to evaluate sensitivity of this technique in CSF in patients with neurological disease.…”
Section: Neuroinvasion By Sars-cov-2mentioning
confidence: 99%
“…Enterovirus D68 (EV-D68) has caused worldwide outbreaks of serious respiratory and neurological disease in 2014 and thereafter. In particular, EV-D68 infection has been associated with acute flaccid myelitis (AFM) (Hixon et al, 2019). EV-D68 was first isolated in 1962, (Schieble et al, 1967) but rarely reported until the recent outbreaks (Centers for Disease Control and Pre- * Correspondence to:…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ICAM-5 was not detected in neonatal mouse spinal cords where EV-D68 is preferentially found (Hixon et al, 2019b). It is possible that a homolog to ICAM-5 is the true neuronal-specific receptor for EV-D68 (Hixon et al, 2019b).…”
Section: Receptors For Neurotropic Enterovirusesmentioning
confidence: 95%
“…Although this receptor is abundantly expressed in neurons (Gahmberg et al, 2008) and shows promise for neuronal-specific tropism of neurotropic enteroviruses, the pattern of EV-D68 infection in brain slice models and microfluidic chamber motor neuron cultures does not correspond to the distribution or expression of ICAM-5 (Hixon et al, 2019a). In fact, ICAM-5 expression in human iPSC-derived motor neuron-like cells was observed within the soma and dendrites while EV-D68 viral particles were observed on the axon terminals (Hixon et al, 2019b). Furthermore, ICAM-5 was not detected in neonatal mouse spinal cords where EV-D68 is preferentially found (Hixon et al, 2019b).…”
Section: Receptors For Neurotropic Enterovirusesmentioning
confidence: 99%
See 1 more Smart Citation